Age-Related Ethnic Differences in Self-Reported Hand Function. (17th December 2021) - Mulayh, Ejlal Bin; Logue, Rachel; Brown, Susan
Abstract: Racial/ethnic differences in the prevalence of disability based on self-reported activities of daily living (ADLs) exist in older Americans, particularly in Hispanic adults. Such studies have relied on large data sets in which disability is measured across a broad range of functional tasks. While useful in generating a global measure of disability, it precludes an ability to differentiate, for example, deficits in upper versus lower extremity function which can provide useful information in targeting therapeutic interventions. Despite known age-related declines in hand function and concomitant ADLs, racial/ethnic differences in hand-related ADL limitations have not been addressed. Using 2011-2018 data from the National Health and Nutrition Examination Survey (NHANES), we identified 3, 189 non-Hispanic White and Hispanic adults aged 65 and older, and classified responses based on perceived difficulty to five self-reported tasks requiring hand dexterity. Compared to non-Hispanic Whites, Hispanic males reported 2.2 times higher rates of difficulty for dressing tasks (p<0.01) and 3.3 times higher rates for difficulties preparing meals (p<0.01). Similar rates of difficulty were also observed in females. Additionally, Hispanic females reported 4.6 times higher rates of difficulty in tasks requiring grasping small objects (p<0.01). Deficits in hand function are often under-reported in older adults despite the role of dexterity in maintaining functional independence. The results presented here indicate that difficulties in hand-related ADLs are more prevalent in the Hispanic population and warrant greater attention in health care settings. Future work will include identifying factors contributing to these observed differences in self-reported difficulties in hand-related ADLs.